Altered Peroxisome Proliferator-Activated Receptor Alpha Signaling in Variably Diseased Peripheral Arterial Segments - Engel, Connor; Meade, Rodrigo; Harroun, Nikolai; Penrose, Amanda; Shafqat, Mehreen; Jin, Xiaohua; DeSilva, Gayan; Semenkovich, Clay; Zayed, Mohamed (Frontiers in Cardiovascular Medicine, 2022)
Objective: Peripheral atherosclerosis manifests in both the extracranial carotid and lower extremity arteries and can lead to significant morbidity. However, atherosclerotic disease progression is often not homogenous and is accelerated by conditions such as diabetes. We previously observed increased phospholipid content in minimally (Min)-diseased carotid arterial segments compared to maximally (Max)-diseased segments. Since Peroxisome Proliferator-Activated Receptor alpha (PPAR; ppara) is a key regulator of lipid metabolism, we hypothesized that it may have increased content and signaling in Min versus Max-diseased arterial segments. Methods: 12 patients who underwent carotid endarterectomy (CEA), and 20 patients who underwent major lower extremity amputation were prospectively enrolled into a vascular tissue biobank. Min and Max-diseased arterial segments were obtained in real-time from the operating room from CEA plaque and arterial segments from amputated lower extremities. mRNA was isolated from all specimens and relative content of PPARA, Acyl-CoA Oxidase 1 (ACOX1), and Carnitine Palmitoyltransferase 1A (CPT1A) were evaluated. Results: We observed significantly higher PPARA expression in CEA segments in patients with diabetes (p < 0.01), as well as higher ACOX1 and CPT1A expression (p < 0.001 and p < 0.05, respectively). Hemoglobin A1c (HbA1c) correlated significantly with PPARA gene expression. In lower leg arterial segments, we observed no difference in gene expression in patients with or without diabetes, but there was significantly increased ACOX1 and CPT1A expression in Max-diseased segments. Although, there was no correlation observed between PPARA expression in lower leg arterial segments and HbA1c, there was a moderate correlation between gene expression and cholesterol levels. Conclusion: This study is the first to evaluate PPARA in variably diseased arterial segments in human carotid and lower extremity arterial specimens. We observed strikingly different expression patterns in PPARA and its downstream genes between human carotid and lower extremity arteries in the setting of diabetes. Our findings suggest that variable gene expression in different arterial tissue may have a differential impact on disease progression and pharmacological targeting strategies.